2014
DOI: 10.1089/neu.2013.3082
|View full text |Cite
|
Sign up to set email alerts
|

Novel Multi-System Functional Gains via Task Specific Training in Spinal Cord Injured Male Rats

Abstract: Locomotor training (LT) after spinal cord injury (SCI) is a rehabilitative therapy used to enhance locomotor recovery. There is evidence, primarily anecdotal, also associating LT with improvements in bladder function and reduction in some types of SCI-related pain. In the present study, we determined if a step training paradigm could improve outcome measures of locomotion, bladder function, and pain/allodynia. After a T10 contusive SCI trained animals (adult male Wistar rats), trained animals began quadrupedal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 112 publications
2
60
1
Order By: Relevance
“…Recent animal studies, however, have shown that LT post-SCI also improves bladder function (46,90), a finding consistent with a few reports from human SCI studies (42,48,75). For example, a recent study from our laboratory (90) has shown, using a spinal contusion model in adult male rats, functional gains of lower urinary tract function as assessed with terminal urodynamic measures after 12 wk of daily LT for a period of 60 min/day. The interaction of lower limb musculature with the bladder and its sphincter has been observed sporadically over the years, as far back as 1933, in both humans and animal studies (20,53,74).…”
supporting
confidence: 84%
See 4 more Smart Citations
“…Recent animal studies, however, have shown that LT post-SCI also improves bladder function (46,90), a finding consistent with a few reports from human SCI studies (42,48,75). For example, a recent study from our laboratory (90) has shown, using a spinal contusion model in adult male rats, functional gains of lower urinary tract function as assessed with terminal urodynamic measures after 12 wk of daily LT for a period of 60 min/day. The interaction of lower limb musculature with the bladder and its sphincter has been observed sporadically over the years, as far back as 1933, in both humans and animal studies (20,53,74).…”
supporting
confidence: 84%
“…Locomotor training (LT) has emerged as a safe and effective therapy for post-SCI motor deficits with many benefits (cardiovascular function, strength, mobility) (9,23,43,52,84). Recent animal studies, however, have shown that LT post-SCI also improves bladder function (46,90), a finding consistent with a few reports from human SCI studies (42,48,75). For example, a recent study from our laboratory (90) has shown, using a spinal contusion model in adult male rats, functional gains of lower urinary tract function as assessed with terminal urodynamic measures after 12 wk of daily LT for a period of 60 min/day.…”
mentioning
confidence: 74%
See 3 more Smart Citations